Supply Chain Management Project on Strategic Development of Enterprises - Elena V. Bokareva; Artur I. Avdalyan (International Journal of Supply Chain Management, 2020)
— In the modern economy, competent strategic supply chain management is the most important and fundamental condition for the success of any organization. The increased attention to the strategic aspects of management is a characteristic feature of the modern enterprise supply chain management, which is associated with solving the problem of the continuous organization development in accordance with the dynamically changing conditions of the external environment.The modern market is highly competitive, uncertain, with high rates of development and a high level of high technology adoption. For effective work in the market, it is necessary to adhere to the elaborated supply chain strategy of enterprise development. The supply chain strategy must take into account current influence and trends in order to be effective and promising. Recently, companies such as Apple, Amazon, and Virgin have developed rapidly and captured markets, harnessing consumers with their goods and services in supply chai n process. The success of these companies is behind their right choice and development supply chain strategy.The relevance of the topic is the elaboration and implementation of the company’s supply chain strategy. After the assessment of the situation, any company needs to take a number of measures to increase its activities. Measures can be different, depending on what information the company had received based on the assessment. There may be measures aimed at improving the advertising strategy, increasing market share, adjusting sales policies, etc. National companies win in the competition with foreign companies by implementing a competent supply chain strategy in the market. The service and other related attributes of companies improve since when elaborating the issue of the development strategy, the quality of the products increases. Thus, with the high competitiveness of enterprises, the stability of the country as a whole is growing.